Pengelolaan Ekowisata Pesisir Lhok Bubon yang Mengintegrasikan Kearifan Lokal dan Prinsip Konservasi Pesisir.onservation Principles Area - Izwar, izwar_123; Izwar, Izwar; Ulhaq, Riza; Saputra, Akmal; Rahmatika Latif, Ikhwan; Yusrizal, Yusrizal (Biotik, 2026)
This study aims to analyze the capacity and balance of Lhok Bubon tourism based on sustainable ecotourism and Acehnese local wisdom. The research approach is sequential, starting with quantitative analysis and then deepened qualitatively. Based on an area of ​​120 hectares, the maximum capacity of the area reaches 20,700 visitors per day with two visit cycles. The marine tourism suitability analysis produces a score of 500 in the suitable category. Supporting parameters include depth in the very suitable category, freshwater sources of sandy beaches, and open land cover also have a very suitable category, the basic material of the coral sand substrate has a suitable category. Constraints found in air clarity are less suitable. For snorkeling and diving, most physical parameters of waves, current speed, pH, salinity, and air clarity are in the S1 (Very Suitable) category, except for coral reef diversity (<25%) which is in the N (Not Suitable) category. Overall, Lhok Bubon Beach is worthy of being developed as an ecotourism habitat, but by helping with coral reef restoration, facilities, and strengthening local values, the novelty in this research is the integration of carrying capacity, tourism suitability, and local wisdom of Aceh, in addition to the quantitative-qualitative sequential approach in assessing coastal ecotourism. Keyword: Coastal Conservation; Ecotourism; Lhok Bubon; Local Wisdom